Beyond antibiotics: phage-encoded lysins against Gram-negative pathogens - Shah, Sanket; Das, Ritam; Chavan, Bhakti; Bajpai, Urmi; Hanif, Sarmad; Ahmed, Syed (Frontiers in Microbiology, 2023)
Antibiotics remain the frontline agents for treating deadly bacterial pathogens. However, the indiscriminate use of these valuable agents has led to an alarming rise in AMR. The antibiotic pipeline is insufficient to tackle the AMR threat, especially with respect to the WHO critical category of priority Gram-negative pathogens, which have become a serious problem as nosocomial and community infections and pose a threat globally. The AMR pandemic requires solutions that provide novel antibacterial agents that are not only effective but against which bacteria are less likely to gain resistance. In this regard, natural or engineered phage-encoded lysins (enzybiotics) armed with numerous features represent an attractive alternative to the currently available antibiotics. Several lysins have exhibited promising efficacy and safety against Gram-positive pathogens, with some in late stages of clinical development and some commercially available. However, in the case of Gram-negative bacteria, the outer membrane acts as a formidable barrier; hence, lysins are often used in combination with OMPs or engineered to overcome the outer membrane barrier. In this review, we have briefly explained AMR and the initiatives taken by different organizations globally to tackle the AMR threat at different levels. We bring forth the promising potential and challenges of lysins, focusing on the WHO critical category of priority Gram-negative bacteria and lysins under investigation for these pathogens, along with the challenges associated with developing them as therapeutics within the existing regulatory framework.